PERAN ORANG TUA DAN GURU PAI DALAM MENGEMBANGKAN PENGENDALIAN DIRI SISWA - Agus Hidayatullah; Ahmad Panji Ruhiyat (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
AbstractIn adolescence precisely puberty. Teens suffer hard times, so need for an effort to teenagers to be able to control yourself from negative acts. The aim of this study was to determine the role of parents and teachers to build on students' pengendalian diri. The theory used is the role of theory. The basic perspective of this theory is that behavior is shaped by the roles assigned by society for individuals to carry it out. and the theory of social interaction. According to Goffman that one of the basic rules of social intearksi is a commitment of mutual reciprocity between the individuals involved regarding the role (role) to be played. This research is qualitative with case study approach in SMPN 4 Pandeglang. As the sample of the research are the students of class VIII which are taken 3 categories based on the students' achievement, discipline, and behavior in each class, that is Baik, Midle, Kurang, The next sample is parents of the studied student, and PAI teacher at SMP N 4 Pandeglang. In collecting the data the researchers used the method of observation, interview, and documentation. The results of this study indicate the existence of truth theory with facts that occur in the field, namely students who belong to the category Kurang. Not get the role of her parents, some are due to divorce factors, living with grandparents, living in boarding schools, and others. In this study the contributing parties include: PAI Teachers SMPN 4 PAndeglang, Students / Students Class VIII SMPN 4 Pandeglang, and Parents of students of Class VIII SMPN 4 Pandeglang.Keywords: Parents, PAI Teachers and Self Control